The sly fox and the chicks - Sommer, Carl, 1930-; James, Kennon (Houston, Tex. : Advance Pub., 2000)
Even though they have been warned not to talk to strangers, some little chicks go with a sneaky fox who promises them a treat.
Keywords: Chickens -- Fiction; Foxes -- Fiction; Strangers -- Fiction